Proceso de ASC - INSTRUMENTACION DEL TELESCOPIO DE LA UNIVERSIDAD EAFIT PARA REALIZAR ESPECTROGRAFIA DE VENUS (2021)
There are indications suggesting that in the past, when the sun was 25% less bright, Venus had conditions similar to present-day Earth, including oceans. However, as the sun increased its brightness, a strong greenhouse effect occurred, leading to significant CO2 release and the eventual evaporation of these seas, resulting in Venus's current atmosphere. Despite these harsh conditions, a region in Venus's atmosphere maintains Earth-like pressures and temperatures, with essential components for life present (1). Subsequent investigations revealed dark patches in Venus's clouds composed of H2SO4 and light-absorbing particles, suggesting the possibility of hosting something akin to Earth's marine algae (2). This information is recent, implying numerous avenues for further research. However, conducting such studies necessitates appropriate instruments, particularly those capable of gathering detailed atmospheric data from Venus. Fortunately, the university already possesses several tools that can facilitate this, including a telescope and a mini digital spectrometer in the optics and photonics laboratory. This setup potentially allows for spectroscopic analysis of Venus's atmosphere by integrating these components and adding supplementary optical instrumentation to enhance data acquisition.